Operational risk management : best practices in the financial services industry - Chapelle, Ariane (John Wiley and Sons, Inc., 2019)
Drawing on the author's extensive experience working with and advising financial companies, this authoritative resource is written both for those new to the discipline and for experienced operational risk managers who want to strengthen and consolidate their knowledge. --